Moderating Role of ESG Reporting in the Association between Green Innovation and Earnings Management in MENA Energy Firms - Hamour, Aiman Abu; Bawaneh, Ahmad Ali Salem; Alhyasat, Khaled M.K.; AlRahamneh, Nour Hussien Yousef; Aburmman, Eman Kamel (International Journal of Energy Economics and Policy, 2026)
This research investigates the impact of green innovation (Gre-inn) on earnings management (EM) in MENA energy companies, taking into account, moderating effect of integrated ESG reporting (ESGC). Based on a sample of 1,747 firm-year observations from the period 2008–2024 results indicate that there is a positive and significant relationship between environmental innovation (Gre-inn) and EM, which implies that environment-driven innovations—triggered by regional clean-energy transitions—can be strategically employed to mold reported performance. ESGC also has a weakly positive effect on EM and reinforces the Gre-inn–EM relationship, suggesting that transparent sustainability disclosure enhances managers’ discretion in managing earnings. Robustness tests validate the findings. These findings are critical for developing MENA economies as both significant reforms and renewable projects along with evolving reporting frameworks are transforming the energy sector.